Passive Thermal Management of Tablet PCs Using Phase Change Materials: Intermittent Operation - Ahmed, Tousif; Bhouri, Maha; Groulx, Dominic; White, Mary Anne (Applied sciences, 2019)
This paper presents an experimental study of thermal management in a tablet PC under intermittent operation, with phase change materials (PCMs) encapsulated in a very thin aluminized laminate film container. It complements a study of the same system under continuous operation that was published in 2018. Two different types of PCMs were used for the experimental work; PT-37 and n-eicosane. A commercially available tablet PC was used as a test subject to ensure representative dimensions and material properties of every intricate part of the real tablet PC. For intermittent operation, the cycle used corresponds to fifteen minutes of operation (heat generation) followed by fifteen minutes of rest, to imitate a regular usage pattern of a tablet PC. It was observed that thin PCM thermal energy storage (TES) units are capable of providing a reduction in the rate of temperature increase during transient operations for both the electronics and the tablet cover. Reduction in peak temperature of the heat source and external surfaces of the tablet PC was also observed. At the maximum of 8 W operating power, PCMs were able to reduce the back-cover temperature by 20 °C. At all power inputs, heat storage in PCMs resulted in back-cover temperatures lower than 40 °C. Moreover, it was found that the PCM thermal management system tested was not affected by the inclination of the tablet PC. Results obtained from this study confirm that thin PCM encapsulation is indeed a suitable solution to control the temperature in tablet PCs during intermittent operation.